2012
DOI: 10.5209/rev_sjop.2012.v15.n3.39390
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Maternal Care Observed in a Group of Brazilian Mothers: an Exploratory Study

Abstract: The aim of this study is to characterize profiles of maternal care in a sample of Brazilian mothers, using a culturalbiological perspective. Participants were 315 women who had at least one child younger than six years-old. They were selected from six Brazilian states. In each state, two groups of mothers were studied, one from the capital and one from a small city. They were interviewed and answered scales on allocentrism, social support, adult attachment, and practices of childcare. Mothers' characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…2 The study identified the experiences of adolescent mothers after the birth of the child, highlighting difficulties such as insecurity, lack of financial and emotional support, and mothers' doubts regarding the differences between professional care and care based on beliefs. 3 It was concluded, in another study with mothers from six Brazilian states, that maternal care is a multidetermined phenomenon 4 , being that the knowledge and care practices of mothers are influenced by the education, economic conditions and culture of the family, community and society. They are experienced by mothers, 3 changes in the psychological aspect, and it is necessary to create coping mechanisms and adaptation to the new condition.…”
mentioning
confidence: 99%
“…2 The study identified the experiences of adolescent mothers after the birth of the child, highlighting difficulties such as insecurity, lack of financial and emotional support, and mothers' doubts regarding the differences between professional care and care based on beliefs. 3 It was concluded, in another study with mothers from six Brazilian states, that maternal care is a multidetermined phenomenon 4 , being that the knowledge and care practices of mothers are influenced by the education, economic conditions and culture of the family, community and society. They are experienced by mothers, 3 changes in the psychological aspect, and it is necessary to create coping mechanisms and adaptation to the new condition.…”
mentioning
confidence: 99%
“…vigentes no contexto mais imediato dos indivíduos (HAGEN, 1999;KELLER, 1997;SEIDL-DE-MOURA et al, 2012). Vale lembrar que na presente tese daremos ênfase a certas variáveis maternas e ecossociais que podem vir a influenciar o IP ou mais especificamente o comportamento materno de cuidados aos descendentes.…”
Section: Variação Do Ip Em Função Do Sexo Do Cuidador: Um Tipo Intensunclassified
“…As diferenças nas estratégias parentais nos diferentes contextos são investigadas por Heidi Keller e seus colaboradores (Keller et al, 2011, assim como por pesquisadores brasileiros (Seidl-de-Moura, et al, 2012b;Silva & Magalhães, 2011;Vieira et al, 2010a;2010b;Macarini et al, 2010;Macarini, 2009;Martins, 2009;Seidlde-Moura, et al,2008;Lordelo, Fonseca & Araújo, 2000), com o objetivo de descrever padrões característicos de um modelo cultural e também o seu impacto para as tarefas de desenvolvimento, por considerar que as experiências sociais iniciais estabelecem as bases para a definição de um self particular que informa soluções para as tarefas de desenvolvimento subsequentes.…”
Section: 4discussão Da Relação Entre Discurso Materno E O Desempenunclassified
“…Ainda, a conformidade maior à vontade/ideia do outro pode adiar a experiência individual de de responsabilidade. No sentido oposto, o incentivo à independência e à expressão de diferentes opiniões e sentimentos pode auxiliar na compreensão de estados mentais e de outro, de que outra pessoa possui opiniões e perspectivas diferentes.A decisão de analisar a interação verbal da mãe com a criança a partir de um referencial de pesquisa intercultural está em consonância com outros estudos brasileiros que procuram identificar singularidades e padrões culturais nos diferentes contextos brasileiros quanto às práticas e crenças de cuidado parental(-de-Moura, et al, 2012b;Silva & Magalhães, 2011;Vieira et al, 2010a;2010b; Macarini et al, 2010;Macarini, 2009;Martins, 2009; Seidl-de-Moura, et al,2008;Lordelo, Fonseca & Araújo, 2000 ) e seus efeitos para o desenvolvimento infantil(Seidl-de-Moura, et al, 2012a). Da mesma forma, essa decisão é consoante com o projeto de De Felipe (projeto de doutorado apresentado ao Instituto de Psicologia em março de 2012), integrante do mesmo projeto temático -IPÊ, que tem como objetivo caracterizar e investigar os potenciais efeitos da DPP aos modelos culturais, etnoteorias maternas (metas de socialização e crenças sobre práticas de cuidado) e práticas maternas adotadas (sistemas parentais).…”
unclassified